Research progress on influencing factors and interventions of post-stroke anxiety (脑卒中后焦虑影响因素及干预措施研究进展) - HOU Jing (侯静) (Association of Integrative Nursing, 2024)
Stroke has seriously threatened the health of all mankind as one of the global public health problems. As a common complication, post-stroke anxiety not only reduces the patient's quality of life , but also increases the risk of stroke recurrence and delays the recovery process. This paper reviews the influencing factors, clinical manifestations, evaluation methods and interventions of post-stroke anxiety, in order to provide a theoretical basis and new ideas for further understanding of post-stroke anxiety and improving patients' anxiety. (脑卒中后焦虑(PSA)是脑卒中患者常见的精神并发症, 不仅影响患者生存质量, 而且可能增加再次脑卒中的风险。本研究对PSA的影响因素、临床表现、评估方法及干预措施进行阐述, 旨在为进一步认识PSA, 改善患者的焦虑情绪, 提供理论依据和新思路。)